The emerging role of circular RNAs in Parkinson’s disease - Liao, Jiajia; Zhang, Qinxin; Huang, Jinjun; He, Honghu; Lei, Jiang; Shen, Yuefei; Wang, Jin; Xiao, Yousheng (Frontiers in Neuroscience, 2023)
Parkinson’s disease (PD) is the second most prevalent neurodegenerative disease and the most common movement disorder. It involves a gradual loss of dopaminergic neurons in the substantia nigra. Although many studies have been conducted, the underlying molecular pathways of PD remain largely unknown. Circular RNAs (circRNAs), a novel class of non-coding RNAs with a covalently closed loop structure, are common in the brain. They are stable, conserved molecules that are widely expressed in eukaryotes in tissue-, cell-, and development-specific patterns. Many circRNAs have recently been identified in nervous system diseases, and some circRNA expression profiles have been linked to PD. Given that recent research has indicated the essential roles of various circRNAs in the development and progression of neurodegenerative diseases, the identification of individual circRNAs may be a promising strategy for finding new treatment targets for PD. Moreover, the search for circRNAs with high specificity and sensitivity will open up new avenues for the early diagnosis and treatment of PD. Herein, we address the biogenesis, properties, and roles of circRNAs and review their potential utility as biomarkers and therapeutic targets in PD.